2020
DOI: 10.1097/olq.0000000000001337
|View full text |Cite
|
Sign up to set email alerts
|

Who Is Practicing Expedited Partner Therapy and Why? Insights From Providers Working in Specialties With High Volumes of Sexually Transmitted Infections

Abstract: Background: Expedited partner therapy (EPT), the practice of prescribing antibiotics for sexual partners of patients, is underutilized in Georgia. This qualitative study in a large urban institution aimed to (1) characterize the clinical specialties that predominantly treat sexually transmitted infections (STIs), (2) identify perceived barriers to EPT, and (3) describe strategies to advance routine EPT use.Methods: Providers in obstetrics/gynecology (OB/GYN), infectious disease (ID), and emergency medicine (EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…This study also identified unique barriers to antibiotic overuse in presumptive or symptomatic treatment without laboratory confirmation, as well as concern for increasing traffic to the ED for STI patients. 23,24…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also identified unique barriers to antibiotic overuse in presumptive or symptomatic treatment without laboratory confirmation, as well as concern for increasing traffic to the ED for STI patients. 23,24…”
Section: Discussionmentioning
confidence: 99%
“…We developed a 21-item survey instrument (Appendix X) including the following sections: demographics, knowledge, attitudes, and behaviors, followed by barriers and facilitators of EPT implementation. The survey instrument was created following a published framework for developing questionnaires 21 and began with discussions with EPT content experts alongside a literature review of published manuscripts on EPT implementation in other practice settings, [22][23][24][25] after which new questions were developed as necessary. We refined the design and content in an iterative process-editing survey versions as needed after each step -through the following steps: (1) a discussion with a survey methodologist expert;…”
Section: Survey Developmentmentioning
confidence: 99%
“…Prior studies have identified lack of health care clinician knowledge and lack of standardized prescriptions as major barriers to advancing expedited partner therapy into routine practice. 6 Our quality-improvement interventions directly addressed these barriers by providing staff education and creation of a standardized clinical workflow. These simple changes have led to improved quality of care for expedited partner therapy, in alignment with recommendations from the CDC, ACOG, and Connecticut’s Department of Health.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike obstetrics and gynecology and infectious diseases, empiric treatment of symptomatic CT/GC is more common in emergency medicine at GHS. 19 Given that treatment is provided before NAAT result availability, there is a risk of overtreatment or undertreatment of infection. Studies in other urban health care systems have shown that 70% to 86% of patients with CT/GC are overtreated with antibiotics in urgent care.…”
Section: Discussionmentioning
confidence: 99%